185 Glycoproteomics Reveals Decorin Peptides with Anti-Myostatin Activity In Human Atrial Fibrillation. (3rd June 2016) - Barreiro, Javier Barallobre; Gupta, Shashi; Zoccarato, Anna; Kitazume-Taneike, Rika; Fava, Marika; Yin, Xiaoke; Zampetaki, Anna; Viviano, Alessandro; Chong, Mei; Bern, Marshall; Kourliouros, Antonios; Domenech, Nieves; et al.
Abstract : Background: Myocardial fibrosis is a feature of many cardiac diseases. We used proteomics to profile glycoproteins in the human cardiac extracellular matrix (ECM). Methods and Results: Atrial specimens were analysed by mass spectrometry after extraction of ECM proteins and enrichment for glycoproteins or glycopeptides. Out of all ECM proteins identified, the small leucine-rich proteoglycan decorin was found to be the most fragmented. Within its protein core, eighteen different cleavage sites were identified. In contrast, no cleavage was observed for biglycan, the most closely related proteoglycan. Decorin processing differed between human ventricles and atria and was altered in disease. The C-terminus of decorin, important for the interaction with connective tissue growth factor, was predominantly detected in ventricles compared to atria. In contrast, atrial appendages from patients in persistent atrial fibrillation had higher levels of full-length decorin but also harboured a cleavage site that was not found in atrial appendages from patients in sinus rhythm. This cleavage site preceded the N-terminal domain of decorin that controls muscle growth by altering the binding capacity for myostatin. Myostatin expression was decreased in atrial appendages of patients with persistent persistent atrial fibrillation and hearts of decorin null mice. A synthetic peptide corresponding to this decorin region dose-dependently inhibited the response to myostatin in cardiac myocytes and in perfused mouse hearts. Conclusion: This proteomics study is the first to analyse the human cardiac ECM. Novel processed forms of decorin protein core, uncovered in human atrial appendages can regulate the local bioavailability of anti-hypertrophic and pro-fibrotic growth factors.